A Program Dedicated to Fortifying Micro, Small, and Medium Enterprises (MSMEs) with the Goal of Promoting Socio-Economic Development and Empowering Women in Rural Rajasthan (International Journal of Food and Nutritional Sciences, 2022)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in fostering thegrowth and progress of the Indian economy, and Rajasthan is no different. In the rural areas ofRajasthan, the MSME sector has been instrumental in generating employment, promoting skilldevelopment, and empowering women